2018
DOI: 10.1161/jaha.117.005733
|View full text |Cite
|
Sign up to set email alerts
|

Novel Patient‐Centered Approach to Facilitate Same‐Day Discharge in Patients Undergoing Elective Percutaneous Coronary Intervention

Abstract: BackgroundSame‐day discharge (SDD) after elective percutaneous coronary intervention is safe, less costly, and preferred by patients, but it is usually performed in low‐risk patients, if at all. To increase the appropriate use of SDD in more complex patients, we implemented a “patient‐centered” protocol based on risk of complications at Barnes‐Jewish Hospital.Methods and ResultsOur objectives were as follows: (1) to evaluate time trends in SDD; (2) to compare (a) mortality, bleeding, and acute kidney injury, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 47 publications
4
31
1
1
Order By: Relevance
“…In a recent study from Barnes Jewish Hospital (St Louis, Missouri) in which we observed a cost savings of approximately $7000 per case of SDD, more than half of the SDD patients actually underwent femoral access, using 85% vascular closure devices. 17 In this study, SDD after femoral access resulted in slightly lower, but still substantial cost savings of $5095 per case.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In a recent study from Barnes Jewish Hospital (St Louis, Missouri) in which we observed a cost savings of approximately $7000 per case of SDD, more than half of the SDD patients actually underwent femoral access, using 85% vascular closure devices. 17 In this study, SDD after femoral access resulted in slightly lower, but still substantial cost savings of $5095 per case.…”
Section: Discussionmentioning
confidence: 60%
“…As hospitals face increasing pressure to provide safe and effective health care at a lower cost, SDD has been described as one strategy to improve the value of PCI. 17 To our knowledge this is the first and only study of contemporary SDD practice in the United States that builds on prior studies of SDD with 3 novel observations. First, not only was the rate of SDD low with a weakly increasing trend, but there was also substantial variation in the practice of SDD across US hospitals, indicating that SDD practices in the United States are essentially random and likely driven by the local culture rather than evidence-based practices.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Acute myocardial infarction is an important cause of morbidity and mortality in the developing 1, 2 3, 4 world [1]. Percutaneous coronary intervention is a common cardiovascular procedure [2]. Primary percutaneous coronary intervention, a mechanical intervention that enables restoration of blood flow by reopening the occluded artery via a catheter with an inflatable balloon, is currently the preferred reperfusion option for acute myocardial infarction with STsegment elevation [3].…”
Section: Introductionmentioning
confidence: 99%
“…7 SDD also enhances hospital resources efficiency, 8 improves cost-effectiveness, and increases patient satisfaction. 9 Despite this, implementation of SDD remains variable worldwide. 10 While the evidence for the safety and effectiveness of SDD is well described in the literature, there is little reported which can be used to help guide the implementation of SDD within complex healthcare systems.…”
Section: Introductionmentioning
confidence: 99%